2010
DOI: 10.1007/s00417-010-1552-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endocanalicular laser dacryocystorhinostomy with and without endonasal procedures

Abstract: Based on our increased anatomical success rates, concomitant endonasal procedures may help increase success rate in endocanalicular diode laser DCR cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
(25 reference statements)
1
27
0
Order By: Relevance
“…Bone-cutting forceps are not required because the diode laser can be applied to ablate the bone. [25] The laser systems achieve satisfactory coagulation and postsurgical edema is not seen with diode laser application. This advantage provides lesser intraoperative bleeding and results in faster wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone-cutting forceps are not required because the diode laser can be applied to ablate the bone. [25] The laser systems achieve satisfactory coagulation and postsurgical edema is not seen with diode laser application. This advantage provides lesser intraoperative bleeding and results in faster wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Wormald et al [26] showed that the major portion of the sac was situated above the middle turbinate and that inadequate bone removal above the middle turbinate is an important reason for failure in all treatment approaches to nasolacrimal ductus obstruction. [25] The endocanalicular approach usually creates smaller neo-ostia than the external and endonasal approaches and this is correlated with lower success rates of endocanalicular DCR. [30] Other reasons for failure of endocanalicular diode laser application are related to formation of synechia between the lateral surface of the middle turbinate and the medial surface of the lateral wall of the nose and the granulation tissue obstructing the neo-ostium.…”
Section: Journal Of Medical Updatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, We read with great interest the controversial report by Basmak et al on the improvement of success rates in initial partial middle turbinectomy (MT) with ECLDCR [1]. The main advantage of ELDCR is the reduction in complications of external and endonasal DCR and improvement of cosmetics.…”
mentioning
confidence: 98%
“…According to Basmak et al [1], partial MT was done for the enlargement of the primary ostium; however, the average diameter of ostium was not mentioned in this article. The diameter of primary external DCR ostium (approximately 1 cm) will be very reduced after the healing process and will measure between 1.8 and 2 mm [8,9].…”
mentioning
confidence: 99%